Roma - a nation without a country = Romowie - naród bez ojczyzny - Adamczyk, Anita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to search for an answer to the question whether the Roma can be considered as a nation? It is not an easy task, as they have never seen them in national terms. After leaving India become cosmopolitans. They have their own culture, language, origin and traditions. Moreover, are equipped anthem and national flag. ere are, howe-ver, the country in which it could waved.
Keywords: Roma; nation; language; Romani institutions; state; Romowie; naród; język; instytucje romskie; państwo